Application of downhole gas compression to improve productivity for depleted natural gas reservoir - Ismail, M.; Hossain, Mofazzal (Australian Petroleum Production and Exploration Association, 2013)
Selection of an optimal artificial lift technology to prolong a depleted gas reservoir has always been a challenge in the oil and gas industry. To be able to have a solution that has low intervention costs and a long operating life is the key. Downhole gas compression (DGC) is the new form of artificial lift technology specifically designed, for gas wells, to increase productivity and maximise the recovery factor of the reservoir. DGC would provide a 20–40% production gain anytime during the production life-cycle of the well. Numerous challenges, however, associated with the design, development and implementation of this new technology are not well understood or documented. Thus, this study has been focused on understanding the key concepts of DGC technology and investigates its potential application for increasing the well productivity of gas wells through sensitivity studies. Emphases are given on the development of a mathematical model that can be used to investigate the effect of reservoir and well operating conditions with the production gain of DGC. This peer-reviewed paper presents the results of some case studies, identifying the key factors associated with the operating condition, well completion, and reservoir properties considered for the successful deployment of such an alternate form of artificial lift method for a gas well based on sensitivity analysis using a developed mathematical model. The sensitivity results confirm a significant gain of well productivity using DGC for certain reservoir and operating conditions.